The effects of surface traction characteristics on frictional demand and kinematics in tennis - Damm, L.; Low, D.; Richardson, A.; Clarke, J.; Carre, M.; Dixon, S. (Sports Biomechanics, 2013)
The interaction between footwear and surfaces influences the forces experienced by tennis players. The purpose of this study was to investigate traction demand and kinematic adaptation during tennis-specific movements with changes in traction characteristics of surfaces. We hypothesised that players would increase the utilised coefficient of friction (horizontal to vertical ground reaction force ratio) when the shoe surface combination had a high coefficient of friction and flex their knee after contact to facilitate braking. Eight participants performed two separate movements, side jump out of stance and running forehand. Ground reaction force was measured and three-dimensional kinematic data were recorded. Clay surface and cushioned acrylic hard court (low vs. high shoe-surface friction) were used. The peak utilised coefficient of friction was greater on clay than the hard court. The knee was less flexed at impact on clay ( - 5.6 ± 10.2°) and at peak flexion ( - 13.1 ± 12.0°) during the running forehand. Our results indicate that tennis players adapt the level of utilised friction according to the characteristics of the surface, and this adaptation favours sliding on the low friction surface. Less knee flexion facilitates sliding on clay, whereas greater knee flexion contributes to braking on the hard court.